Immune Response Activation and Immunomodulation 2019
DOI: 10.5772/intechopen.80545
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated Red Blood Cells Contribute to the Host Immune Response Against Pathogens

Abstract: It has recently come to light that nucleated red blood cells (RBCs) of fish, amphibians, reptiles and birds are multifunctional cells, because in addition to being involved in gas exchange and transport, it has also been reported that they respond to pathogens by means of (i) phagocytosis, (ii) antigen presentation, (iii) production of cytokines and antimicrobial peptides, (iv) regulation of complement system, and (v) exerting paracrine molecular communication with other immune cells and modulating their funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Notably, we observed a small part of nucleated erythrocytes unexpectedly expressing signatures related to innate immune (neutrophil, phagocytosis and inflammatory response) and adaptive immune (antigen processing and presentation) reactions. It has been reported that nucleated erythrocytes of human cord blood suppressed the production of inflammatory cytokines from monocytes in a lipopolysaccharide (LPS)-mimicked system, to avoid a vigorous innate immune reaction [ 24 ]. Our results from adult bone marrow further confirmed the mediator roles of nucleated erythrocytes in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we observed a small part of nucleated erythrocytes unexpectedly expressing signatures related to innate immune (neutrophil, phagocytosis and inflammatory response) and adaptive immune (antigen processing and presentation) reactions. It has been reported that nucleated erythrocytes of human cord blood suppressed the production of inflammatory cytokines from monocytes in a lipopolysaccharide (LPS)-mimicked system, to avoid a vigorous innate immune reaction [ 24 ]. Our results from adult bone marrow further confirmed the mediator roles of nucleated erythrocytes in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleated red blood cells (RBCs) of fish contain the transcriptional and translational machinery necessary to produce characteristic molecules of the immune system to respond against various infectious agents and play an active role in maintaining homeostasis of the fish immune system [95]. The nucleated RBC are reportedly involved in both innate and adaptive immune responses in fish [96]. Nucleated RBCs are able to phagocytose, acts as antigen-presenting cells [97,98], recognizes pathogen associated molecular pattern (PAMPs) by specific pathogen recognition receptors (PRRs), modulate leukocyte activity, release cytokine-like factors [99,100] and also induces interferon in fish [101].…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…Avian nucleated red blood cells (RBCs) contain transcriptional and translational requirements for producing the characteristic molecules of the immune system to defend against pathogenic attacks. Therefore, nucleated RBCs seem to be involved in the regulation of both innate and adaptive immune responses, which highlights the crucial role of RBCs in host defence against pathogens [ 19 ]. To the best of our knowledge, there are no reports on gene expression in peripheral blood cells in nematode-infected chickens with different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%